GPER Enhances Chronic Burn Pain via PKC-Mediated Mu-Opioid Receptor Phosphorylation in the Rostral Ventromedial Medulla - Zhu X; Zhang Y; Zhang Q; Zhang Z (Journal of Pain Research, 2025)
Xunxi Zhu,1,2 Yajun Zhang,1,2 Qiqi Zhang,1,2 Zhongjun Zhang1,2 1Department of Anesthesiology, Affiliated Hospital of Jiangnan University, Wuxi, People’s Republic of China; 2Wuxi Medical School, Jiangnan University, Wuxi, People’s Republic of ChinaCorrespondence: Zhongjun Zhang, Email wuxizzj@163.comObjective: Chronic pain following burn injury represents a formidable challenge in analgesic management, as the complex interplay and dynamic nature of multiple neural mechanisms underlying abnormal hyperalgesia renders its resolution exceptionally problematic. The G protein-coupled estrogen receptor (GPER) located within the rostral ventromedial medulla (RVM) has been recognized as a critical element in regulating descending pain signal transmission throughout the brain. Nevertheless, the precise underlying mechanisms remain insufficiently elucidated. This investigation examined GPER function in chronic pain modulation and its role in pain rehabilitation.Methods and Results: A murine model of burn injury-induced chronic pain was employed, wherein nociceptive paw withdrawal reflexes to both thermal and mechanical stimuli were evaluated. In contrast to mice exhibiting pain resolution, a subset displaying sustained or stimulus-evoked reductions in pain threshold developed a persistent pain phenotype. Notably, prolonged hyperalgesia post-burn injury was associated with GPER activation. GPER-immunoreactive neurons were found to be co-localized with activated protein kinase C (PKC) and μ-opioid receptor (MOR) in murine tissues. Moreover, in mice with persistent pain, phosphorylation of MOR—facilitated by activated PKC rather than GRK 2/3—was implicated in GPER-dependent nociceptive allodynia, a process effectively reversed by selective PKC inhibition. In these animals, attenuation of PKC activation significantly elevated the pain threshold by inhibiting MOR phosphorylation.Conclusion: These findings highlight the involvement of GPER-dependent PKC-mediated MOR phosphorylation in RVM during postoperative chronic pain development. These insights may contribute to an enhanced understanding of chronic pain’s fundamental mechanisms and suggest potential preventive approaches for analgesic interventions.Keywords: chronic pain, G protein-coupled estrogen receptor, mu-opioid receptor, protein kinase C